A Survey on the Understanding and Viewpoints of Renewable Energy among South African School Students - Daniel Raphael Ejike Ewim; Sogo Mayokun Abolarin; Temiloluwa Olatunji Scott; Chidebe Stanley Anyanwu (The Journal of Engineering and Exact Sciences)
Renewable energy has become an essential component for the survival of human beings. This is because conventional energy supply is limited, nearing its limits, and or destroying our environment. The complete transition to renewable energy is a major approach to achieving sustainable and clean energy distribution progress in this ever-changing and demanding world. This research work investigates the knowledge of renewable energy among the youth and their understanding of sustainable energy prosperity towards meeting the future generation's energy needs. To achieve this, a set of questionnaires was developed to identify their knowledge of various renewable energy resources, energy aspects, applications, and the extent to which the current syllabus provides a well-developed background. They were administered to high school students in KwaZulu-Natal, Durban. The main findings of this investigation reveal that the students were most familiar with solar energy, which could be due to the increasing availability of solar panels across the nation. However, a lack of awareness and little understanding of geothermal energy was noted among the high school students. This indicates a poor future for its development. Furthermore, 86% of the students agreed that conventional energy sources would likely still be relied upon by a significant portion of the global population to meet daily energy needs. Therefore, the government must take swift action to address these issues, by promoting the deployment of renewable energy sources in schools.